Diagnóstico sócioambiental da atividade de fabricação da cal em fornos artesanais no município de Frecheirinha/Ce - Andrade, John Kennedy Candeira (2005)
The State of Ceará possesses according to data of the Atlas of Human Development in Brazil, an Index of Municipal Human Development (IDH-M), of 0,7 occupying the 20th placement in the ranking of the 26 Brazilian states plus the Federal district. And 75% of the State’s area is under adverse climate conditions, with annual precipitations below 800 mm. Besides the irregularity of the precipitations, it presents drought cycles of 8 or 12 years, being under the influence of the semi-arid climate 49,69% of the State’s total area. Among its municipal districts is the one of Frecheirinha, located at 286,3 km distant from Fortaleza, in the northwest portion of the State, with a population of 11.832 and with an IDH-M 0,605, that it puts it in the 140th place among the 184 municipal districts of the State and in the 4.584th place in relation to the 5.561 Brazilian municipal districts. It is in this municipal district, and under these adverse climatic and socioeconomic conditions, that grows the activity of production of the whitewash in craft ovens (lime pits), in establishments that are characterized by informality, and that obtain calcite originating from irregular extraction areas. There the wood is also extracted, transported and acquired in an irregular way in order to be used as firewood in the transformation of the calcite blocks in whitewash, generating an entropic action of devastation of the native vegetable covering (savanna). This activity produces atmospheric pollutants, with rudimentary industrial techniques and the working conditions are unhealthy and expose the workers to several risk agents and occupational diseases. The general objectives of this study are to diagnose the social and environment impacts generated by the activity of production of the whitewash in craft ovens in the municipal district of Frecheirinha, and to propose alternative solutions based on the sustainable endogenous development. The specific objectives of this study are: to describe the socioeconomic profile of the units that compose the sample; to identify the hygiene and safety conditions of the work in the selected lime pits; to analyze the identified adverse social and environment impacts and to study alternative projects of sustainable endogenous development. To elaborate this study, it was adopted literature research and cartographic study, the methodological procedure of the field research or more specifically of the participant research of Malinowski, which is characterized by the researcher's insertion in the reality that he intends to study. To proceed, it was used the non probabilistic sampling process of the intentional type or of judgment. In a universe of nine such establishments located in Frecheirinha, were chosen the five more representative in relation to the requirements: amount of active ovens, number of workers direct or indirectly involved in the activity, firewood and calcareous rock consumption and the amount produced monthly. The collected data, tabulated and analyzed indicate: work day of up to 12:00 hours in shifts of day and night, 72% of the workers without signed wallet; The researched workers' education profile is characterized by an average of 3,7 years of study; 24% never went to a school or did so for just a few months; 50% studied for a period of 1 to 4 years; and 26% for a period of 5 to a maximum of 8 years. The level of acquired knowledge varies as follows: 50% don’t know how to read nor to write; 37% affirm to know how to read and/or to write a little; and 12% answered that they know how to read and to write. There is incidence of cases of alcoholism associated to the use of other stimulating drugs; dermatitis; absence of EPIs and EPCs; illegal extraction, transportation and consumption of 864m3/month of firewood of the native forest (savanna); extraction of 1.440 ton/month of calcite. The viable endogenous alternative proposals are: the honey production in associations, due to the apiary potential of the area and partner-environmental sustainability; the creation of a pole of mineral crafts and the tourist visitation induced by the attraction of ecological and scientific trails, rocky formations and living rooms.